Diversity and abundance of ladybird beetles in selected agricultural fields of Sivakasi in relation to weather factors - Sundareswari, C.; Sudarmani, D.N.P.; Durkga, S. Jaya (International Journal of Scientific Research in Biological Sciences, 2019)
The coccinellidae are a significant group of beetles from both as biological control agent and in their diversity and adaptation to a number of differing habitats. The coccinellid beetles are considered to be a great economic importance in agro-ecosystem through their successful role in the biological control of many injurious insect. From a realistic point of view, the family includes many important predators of insect pests such as aphids and scales. In the present study the assemblages of coccinellid beetles in various agricultural environments are studied and the biodiversity of ladybird beetles was correlated with weather parameters. The objectives of the present study were to explore the predatory ladybeetle fauna of Sivakasi, to estimate the species richness, species evenness and species dominance of coccinellids in the agro-ecosystem.